Λ+c production and baryon-to-meson ratios in pp and p-Pb collisions at √sNN=5.02 TeV at the LHC - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Bergmann, Luisa; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Kroesen, Martin; Pachmayer, Yvonne C.; et al. (Physical review letters, 2021)
The prompt production of the charm baryon Λ+c and the Λ+c/D0 production ratios were measured at midrapidity with the ALICE detector in pp and p-Pb collisions at √sNN=5.02  TeV. These new measurements show a clear decrease of the Λ+c/D0 ratio with increasing transverse momentum (pT) in both collision systems in the range 2<pT<12  GeV/c, exhibiting similarities with the light-flavor baryon-to-meson ratios p/π and Λ/K0S. At low pT, predictions that include additional color-reconnection mechanisms beyond the leading-color approximation, assume the existence of additional higher-mass charm-baryon states, or include hadronization via coalescence can describe the data, while predictions driven by charm-quark fragmentation processes measured in e+e− and e−p collisions significantly underestimate the data. The results presented in this Letter provide significant evidence that the established assumption of universality (colliding-system independence) of parton-to-hadron fragmentation is not sufficient to describe charm-baryon production in hadronic collisions at LHC energies.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Im Titel ist das Zeichen + hochgestellt
Im Titel ist der Buchstabe c tiefgestellt
Gesehen am 25.01.2022
*ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, A. Berdnikova, L. Bergmann, M.C. Danisch, V.J.G. Feulliard, P. Glässel, J. Kim, M. Kim, M. Kroesen, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, S.F. Stiefelmaier, B. Windelband [und 986 weitere Personen]